Management of a Common Iliac Artery Aneurysm Causing Contralateral Iliac Venous Thrombosis - Miron Fasoulakis; Alexandros Blionas; Evridiki Karanikola; George Galyfos; Emannuel Barbaressos; Konstantinos Filis (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2015)
A 73-year-old male patient was diagnosed with thrombotic obstruction of the left common iliac vein (LCIV). Computed tomography imaging revealed a known -under follow-up- isolated aneurysm of the right common iliac artery that seemed to directly obstruct the LCIV. Given the patient's renal insufficiency as well as the size and anatomy of the aneurysm, the patient underwent open repair. The decision between open and endovascular repair, given the proximal DVT, is a dilemma, considering the risk for pulmonary embolism perioperatively as well as the venous thrombosis outcome postoperatively. Therefore, we present such an unusual case and discuss proper management.